Pengaruh Pendapatan dan Konsumsi Rumah Tangga terhadap Kesejahteraan Keluarga Petani Penggarap Sawit di Kecamatan Kumpeh Kabupaten Muaro Jambi - M Alhudhori; Muhammad Amali (J-MAS (Jurnal Manajemen dan Sains), 2020)
The consumption activities of each family have different spending types. The difference in consumption patterns in each family is used as a burden or dependents in fulfilling the needs of all family members, so that it is used as a measure of the family welfare evenly and intact. Rural populations have higher levels of consumption compared to urban populations. Welfare in the essence of fulfillment of all needs by doing consumption activities, which are filled with income that has to achieve satisfaction. The purpose of this research is to know the influence of income and household consumption to the welfare of smallholder farmer family in Kumpeh sub-district of Muaro Jambi. The results of this study revealed that the income and household consumption jointly influence positive and significant to the welfare of the farmer family of oil palm farmers in Kumpeh sub-district Muaro Jambi